# algebra

Solve with fractions.

6x^(2/3)-11x^(1/3)+4=0

How do I solve? Thanks

1. 👍 0
2. 👎 0
3. 👁 149
1. let x^(1/3)=a
6a^2-11a+4=0
a=0.5, a=4/3
x=1/8, x=64/27

1. 👍 0
2. 👎 0

## Similar Questions

1. ### Algebra 2

I'm working on Lesson 6: Absolute Value Equations and Inequalities Algebra 2 A Unit 2: Expressions, Equations, and Inequalities and feel confident in my first few answers, but beyond that am lost. May I have some help? **=the

2. ### Mathematics

Solve the simultaneous equations, giving your answers in base two. 11x +11y =1001 10x - y =11 Pls help

3. ### trigonometry

Solve the following equation for all solutions: sin(6x)cos(11x)-cos(6x)sin(11x)=-.1

4. ### math

solve the simultaneous equation, giving your answer in base 2 11x+11y=1001 10x -y =10

1. ### Math

1. Which ordered pair is a solution of the equation y = −11x + 4? a. (0, -7) b. (-1, -7) c. (1, -7) d. (2, 26) MY ANSWER: C Because (X,Y) so -11x = -11 * 1 = -11 -11 + 4 = -7 2. A plumber charges \$65 per hour to fix a leak. What

2. ### college algebra

Solve for 3x + 6Y - 9z = 3 5x - 7y + 10z = -4 11x +4y - 6z = 2

3. ### Maths

solve the following using quadratic formula 2x^2 - 11x 12=0?

4. ### Alebra

Solve 5m - 8 > 12 Solve 12 - 3a > 18 Solve 5m - 4 < 2m + 11 Solve 2r - 18 ≤ 5r + 3 Solve 26p - 20 > 14p + 64 Can someone give me an example to one of these? I don't know how to do these.

1. ### math

Jenny wanted to solve the quadratic equation x2 - 11x +18 = 0 by factoring. Which of the following equations would lead her to solve the given equation?

2. ### algebra

explain how you solve 11x=3y=12 using 3x=9 as subsitution

3. ### algrebra

Iḿ doing a sensitivity analysis in the contants of the constraints 3+4y=40+h 2x+1y=20 2x+3y=60 I need to solve for x ....I know what to do later...I have to solve for y and then I have to solve for h in terms of X and Y.. so I

4. ### math

I have a linear equation problem I am trying to solve that has fractions in it - (x - 2)/5 - (x - 4)/2 = 2 To solve, I first find the lcd which is 10, then multiply everything by 10, so: 10(x - 2)/5 - 10(x - 4)/2 = 2 * 10 This